Effectiveness Of Clinical Parameters And Laboratory Values In Predicting The Clinical Course of Sarcoidosis - Deniz Çelik; Sertan Bulut (Acta Medica Alanya)
Aim: The natural course of sarcoidosis is heterogeneous. There is no clear marker that can predict the course of this disease and its characteristics over months/years. We aimed to analyze our patients' data to identify a prediction parameter at admission.Methods: The patients with sarcoidosis and followed-up between 01/01/2015 and 31/12/2020 comprised the study group. The patients were staged by a Scadding staging system. Improvement or deterioration in at least two of the clinical-laboratory-radiological parameters indicates regression, stable disease, progression, or relapse of sarcoidosis.Results: The study group comprised 4 cases (6.9%) defined as stage 0; 15 cases (25.86%) as stage 1; 39 cases (67.24%) were defined as stage 2. The mean age at diagnosis was 40.84±13.56 in stage 0 + stage 1 group, while it was 48.05±13.36 in the stage 2 group (p=0.06). 74.1% of the cases were women. The female/male ratio was found at 2.86. 57 out of 58 cases had a pathological diagnosis (EBUS TBNA). While PFTs values and DLCO were significantly lower at advanced stages but the same statistical significance was not identified between these values and the clinical course of the disease. As a result of the multivariate analysis, it was observed that only the presence of chest pain at admission affected the progression of the disease in the follow-up period.Conclusion: Sarcoidosis is a multi-systemic disease and there is no clear finding for predicting the poor prognosis of the disease. We conclude that chest pain symptom at admission is valuable predictive finding and can be used as a clue for the progression at follow-up.